THE EFFECT OF CROSS FIT TRAINING ON SOME PHYSICAL AND PHYSIOLOGICAL ABILITIES AND THE ACHIEVEMENT OF 400-METER MEN'S RACE - Dr. Wael Abdullah Hussein Al-lami (Scholars Digest Publishing, 2024)
The introduction of the research dealt with identifying the effect of CrossFit training on some physical and physiological abilities and the achievement of 400 meters for men, as the research sample consisted of an elite group of players from the Army Sports Club who won advanced positions in the official Iraqi athletics championships. The number of sample members was (10) players who were deliberately selected from the research community and were randomly divided into two groups, with (5) for the control group and (5) for the experimental group, as the researcher used the experimental method, which is considered the closest to obtaining results, and the application of the method took (10) weeks with two training units distributed during the week, and the results of the study showed that the application of the CrossFit training program had a positive effect on developing the physical characteristics of the legs as well as some physiological variables (resting pulse, effort pulse) and also a noticeable development in the digital level (achievement). The researcher recommended the necessity of using this type of CrossFit training and including it in training units because of its effective impact on developing players in various sports.
Keywords: CrossFit, physical abilities, physiological abilities, achievement, 400m runner.